Skull Base Invasion Patterns of Malignant Head and Neck Tumors: A Neurosurgical Perspective - Iwami, Kenichiro; Fujii, Masazumi; Nishio, Naoki; Maruo, Takashi; Fujimoto, Yasushi; Takanari, Keisuke; Kamei, Yuzuru; Yamada, Masayuki; Ogawa, Tetsuya; Osuka, Koji; Saito, Kiyoshi (Journal of Neurological Surgery Part B: Skull Base, 2020)
Objective Craniofacial resection (CFR) and temporal bone resection (TBR) on malignant head and neck tumors (MHNTs) invading skull base require accurate and precise determination of the tumor invasion. We investigated tumor skull base invasion patterns and surgical results in CFR and TBR cases.Methods We performed either CFR or TBR for 75 selected patients with the possibility of en bloc resection over the period between 2011 and 2018. The medical charts of the selected patients were reviewed.Results Primary tumor onset site (TOS) groups were: (1) nasal cavity/ethmoid sinus, 20 cases; (2) orbit, 10 cases; (3) maxillary sinus, 28 cases; and (4) external ear/temporomandibular joint, 17 cases. Grades for tumor invasion depth (TID) included: (I) extracranial invasion and skull base bone invasion; (II) extradural invasion; or (III) intradural invasion. Patients in groups 1 and 2 had a significantly higher frequency of grade II and III invasions than patients in groups 3 and 4. The main invasion site was nasal cavity superior wall and ethmoid sinus superior wall for group 1 tumors, orbit superior wall, and lateral skull base sphenoid bone for group 2 and 3 tumors, and lateral skull base temporal bone for group 4 tumors. Positive resection margins represented a significant negative prognostic factor. TID and TOS did not affect skull base margin status.Conclusion Skull base invasion of MHNTs exhibits certain fixed patterns in sites susceptible to invasion based on the TOS. The frequencies of extradural and intradural invasions differed, indicating the importance for accurate preoperative tumor evaluation.
Keywords: en bloc resection; malignant head and neck tumor; skull base invasion; outcomes